Analisis Kinerja Karyawan pada PT X - Fathin, Anisyah; Wolor, Christian Wiradendi; Utari, Eka Dewi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze employee performance at PT X by highlighting three main aspects, namely the level of job satisfaction, factors that affect performance, and the role of feedback in improving productivity. In this study, a qualitative approach was applied through a case study method, with data collection techniques including in-depth interviews, direct observation, and documentation with four key informants, consisting of one head of HR and three non-HR employees. The results showed that the majority of employees were satisfied with their jobs, especially when the job was in line with their educational background, supported by a conducive work environment, and provided opportunities for self-development. Nevertheless, there are some obstacles that hinder the optimization of performance, such as the lack of clarity in the division of tasks in the newly formed unit, rewards that have not been well structured, and a feedback system that has not been running regularly and personally. Factors that influence performance include leadership effectiveness, teamwork, role clarity, reward system, adequate training, and availability of work facilities. Therefore, this study recommends the need to strengthen a more systematic and responsive performance management system, including the development of a sustainable reward system and the implementation of regular two-way feedback to encourage continuous improvement in employee motivation and performance.